크리스토펠 기호
http://bomber0.myid.net/ (토론)님의 2010년 1월 11일 (월) 15:04 판
- 제1기본형식을 이용한 표현
\(\Gamma^1_{11}=\frac{GE_u-2FF_u+FE_v}{2(EG-F^2)}\)
\(\Gamma^1_{12}=\frac{GE_v-FG_u}{2(EG-F^2)}\)
\(\Gamma^1_{22}=\frac{2GF_v-GG_u-FG_v}{2(EG-F^2)}\)
\(\Gamma^2_{11}=\frac{2EF_u-EE_v-FE_u}{2(EG-F^2)}\)
\(\Gamma^2_{12}=\frac{EG_u-FE_v}{2(EG-F^2)}\)
\(\Gamma^2_{22}=\frac{EG_v-2FF_v+FG_u}{2(EG-F^2)}\) - \(F=0\) 인 경우
\(\Gamma^1_{11}=\frac{E_u}{2E}\)
\(\Gamma^1_{12}=\frac{E_v}{2E}\)
\(\Gamma^1_{22}=\frac{-G_u}{2E}\)
\(\Gamma^2_{11}=\frac{-E_v}{2G}\)
\(\Gamma^2_{12}=\frac{G_u}{2G}\)
\(\Gamma^2_{22}=\frac{G_v}{2G}\)